Effects of special muscle stretching on the ball-speed at driver swing of amateur golf players - Kim, J. M.; Yoon, S. D.; Seong, D. H.; Park, G. D.; Kim, S. J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Purpose: In the present study, therefore, stretching exercises were performed by the subjects in order to examine their effects on golf swing-related factors that can be easily influenced by continuous and long-term repetitive movements, unstable postures, and excessive force. The study goal was to examine the effectiveness of stretching exercises for improved swing. The study investigated stretching for a safer golf swing compared to present stretching methods for a proper swing in order to examine the effects of stretching exercises on golf swings. [Subjects] The subjects were 20 amateur golf club members who were divided into two groups: an experimental group which performed stretching, and a control group which did not. The subjects had no bone deformity, muscle weakness, muscle soreness, or neurological problems. Methods: A swing analyzer were used as the measuring tools. The swing analyzer was a GS400-golf hit ball analyzer (Korea). Results: Hit-ball speed at golf driver swings were measured and the results show there was an increase of approximately 5m/s from 67.30±5.40m/s before the intervention to 72.00±4.73m/s at 12 weeks in the experimental group, but there was little change from 66.30±4.78m/s before the intervention to 67.90±4.81m/s at 12 weeks (Table 3)in the control group. Two-way repeated ANOVA the results show there were no interaction effects but there were significant differences (p<0.05) between the groups (F=5.95, p<0.05). Conclusion: To examine the effects of a special stretching program for golf on golf swing-related factors, 20 male amateur golf club members performed a 12-week stretching training program.